2002
DOI: 10.1021/bi0121860
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Structure and Dynamics of the Dinuclear Zinc β-Lactamase Site from Bacteroides fragilis

Abstract: Herein, we report quantum chemical calculations and molecular dynamics (MD) simulations of the dinuclear form of the Bacteroides fragilis zinc beta-lactamase. We studied four different configurations which differ in the protonation state of the Asp103 residue and in the presence or absence of a Zn1-OH-Zn2 bridge. The flexibility of the Zn1-OH-Zn2 bridge was studied by means of quantum mechanical (QM) calculations on cluster models while the relative stabilities of the different configurations were estimated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 52 publications
5
102
1
Order By: Relevance
“…21, 2009 10047 hydrogen bonding interactions decrease the pK a of a terminally zinc bound water by up to 2.5 pH units. 105 The presence of water and hydroxide ligands are supported by the mass spectrometry conducted under kinetic solvent conditions, and similar hydrogen bonding interactions are proposed in metallohydrolases such as leucine aminopeptidase, 108 β-lactamases, 109 GdpQ, 94 and have been studied in binuclear zinc 107,110,111 and nickel 112 complexes.…”
Section: Articlementioning
confidence: 87%
“…21, 2009 10047 hydrogen bonding interactions decrease the pK a of a terminally zinc bound water by up to 2.5 pH units. 105 The presence of water and hydroxide ligands are supported by the mass spectrometry conducted under kinetic solvent conditions, and similar hydrogen bonding interactions are proposed in metallohydrolases such as leucine aminopeptidase, 108 β-lactamases, 109 GdpQ, 94 and have been studied in binuclear zinc 107,110,111 and nickel 112 complexes.…”
Section: Articlementioning
confidence: 87%
“…is conserved in the active sites of all known MBLs and is the residue that coordinates to Zn2. Suá rez et al (33) and Oelschlaeger et al (46) reported that the Zn-Zn distance could possibly increase to 4.5-5.0 and 4.3-5.2 Å by using CcrA and IMP-1 in the substrate complex as a model in molecular dynamics simulations, respectively. This suggests that His-263(197) is flexible, to some extent, and this flexibility may cause an increase in the Zn-Zn distance.…”
Section: Discussionmentioning
confidence: 99%
“…In the threedimensional structure of CcrA, reported in 1996, Concha et al (28) (32) predicted that the Zn2-bound Asp-120 in CcrA could participate as a proton shuttle or proton donor. Moreover, Suá rez et al (33) proposed that the unprotonated Asp-120 results in the rapid formation of a rigid Zn1-OH-Zn2 linkage, whereas the neutral Asp-120 is compatible with a fluctuating Zn1-Zn2 distance through the breaking and/or formation of the Zn1-OHZn2 bridge.…”
mentioning
confidence: 99%
“…[14,17] The latter has been reproduced by a shared water/hydroxide structure B in quantum chemical studies and molecular dynamics (MD) simulations for the B. fragilis and B. cereus enzymes in their free and substrate-complexed forms, [19][20][21] and such a more flexible nonbridged form (B) may best be described as an O 2 H 3 unit between the two zinc ions. The Zn···Zn separations are hence found to vary between 3.4 (A) and 4.4 (B).…”
Section: Introductionmentioning
confidence: 98%
“…[24] While the exact identity and position of the nucleophile is unclear, calculations led to the proposal that substrate binding may induce rupture of the hydroxide bridge and an increase in Zn···Zn separation in order to enhance nucleophilicity of the hydroxide group. [19][20][21] The pH profiles of the B. cereus reaction indicate that the second zinc(ii) is not required for nucleophile activation, but it has been proposed that it may play a role in orienting the attacking nucleophile and in stabilizing reaction intermediates. [24,[26][27][28] A ringopened form of the substrate could be detected as an intermediate in the hydrolysis of nitrocefin by the B. fragilis enzyme, [29] and its identity as a zinc(ii)-bound N-deprotonated species that results upon CÀN bond-cleavage has been corroborated by model studies.…”
Section: Introductionmentioning
confidence: 99%